Ser adolescente, pobre e pai: um estudo qualitativo das repercussões na organização das famílias - Paiva, Maria de Fátima Souza de (2003)
The early fatherhood in low income family requires structural adaptations from many factors such as change and adaptation of roles related to psychosocial and family aspects. This subject has been discussed to a low extention through scientific papers. When it is found, it usually appears to have an unfavorable consequence. From the 80 s, this vision started to be treated through a new perspective, by the inclusion of the male adolescent participation in the reproductive process. Thereby, this study aims to understand the adolescent fatherhood repercussion on the organization of low income families. Besides, it aims to understand the changes that the fatherhood brought to the adolescent and his family on his life project (study, work and social relationships), as well as to verify the possible changes in relation to the adolescent parents in a point of view of family roles. In this study, eight families were evaluated, being three of that used in the first phase and the other five ones in the research effective phase (second phase). In both phases, it was applied an individual interview to each one of the participants (adolescent and his parents, uncles and grandparents which have parent role). As inclusion critery it was selected primary adolescents 16 to 19 years old, with a son (or daughter) three months to one year old. The participants are from low income families, living in Recife- PE periphery. The interviews were recorded, written and analized according to the objectives and understanding of General Systems Theory. The results pointed out the family and social support as fundamental factors on the adolescence fatherhood transition process. It also showed that it brings a suffering to the father adolescent due to the necessity of living his love and corresponding to the necessities of the providing role. The solution of this conflict will have a favorable impact on the way of understanding adolescence fatherhood, future of the father adolescent, his son, and the relationships that this father is able to establish